Tender Evaluation Improvement at PT. X Using Analytical Hierarchy Process - Athina Sakina Ratum; Chikita Lestari Sianipar; Andira Taslim (President University, 2021)
A project is part of the activity done by the company in order to achieve its business goal. One of the activities inside a project is tendering to ensure the availability of the resources needed for the project is fulfilled. PT. X is one of the companies that implement the tendering process to achieve its business goal. One of the operations that require the tendering process is the security operation. The tender announcement is made for the public for any vendors able to fulfilled the requirement can apply for the tender and follow the selection process. The selection process is conducted by the procurement committee and the contract engineer. They determined the tender evaluation criteria and give scores to each of the criteria. In the current condition, the determination of the weight is prone to subjectivity due to the non-existence of any quantitative method in the decision-making process. This study proposes the use of the Analytical Hierarchy Process (AHP) as a tool to help the company to determine the criteria, sub-criteria, and each of the weights as the quantitative method. This method reduces the subjectivity factor and ensures a structured decision-making framework. The winner of the tender from this study and the current condition are the same. However, the final score is different, and the vendor with the lowest score is also different. This difference is due to the different weights in the current condition and this study.